2007
DOI: 10.1097/phm.0b013e31813e0de0
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation as an Adjunct to Constraint-Induced Therapy

Abstract: Objective-To test the potential adjuvant effect of repetitive transcranial magnetic stimulation (rTMS) on motor learning in a group of stroke survivors undergoing constraint-induced therapy (CIT) for upper-limb hemiparesis.Design-This was a prospective randomized, double-blind, sham-controlled, parallel group study. Nineteen individuals, one or more years poststroke, were randomized to either a rTMS + CIT (n = 9) or a sham rTMS + CIT (n = 10) group and participated in the 2-wk intervention.Results-Regardless o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
138
2
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(158 citation statements)
references
References 30 publications
6
138
2
12
Order By: Relevance
“…Notably, a previous study in which constraint-induced movement therapy was administered (consecutively, but not simultaneously) with rTMS revealed no significant differences between real and sham stimulation on motor function of chronic stroke patients. 8 Thus, the concurrent modulation of cortical excitability and peripheral sensorimotor stimulation has the potential to enhance motor improvement and corresponding plastic changes more significantly than any one intervention by itself.…”
Section: Figure 3 Contrast Of Affected Limb Movements Postinterventiomentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a previous study in which constraint-induced movement therapy was administered (consecutively, but not simultaneously) with rTMS revealed no significant differences between real and sham stimulation on motor function of chronic stroke patients. 8 Thus, the concurrent modulation of cortical excitability and peripheral sensorimotor stimulation has the potential to enhance motor improvement and corresponding plastic changes more significantly than any one intervention by itself.…”
Section: Figure 3 Contrast Of Affected Limb Movements Postinterventiomentioning
confidence: 99%
“…5,6 The model of interhemispheric imbalance provides a framework for developing hypotheses based on its 2 facets: 1) upregulating excitability of intact portions of the ipsilesional motor cortex and 2) downregulating excitability of the contralesional motor cortex to modulate its unrestrained inhibitory influence on ipsilesional regions. 2,4 Pilot and proof-ofprinciple studies, using either rTMS [7][8][9][10] or tDCS, [11][12][13][14] have shown both approaches to have beneficial effects on motor skills and motor learning. Furthermore, the combination of tDCS and peripheral stimulation (e.g., peripheral nerve stimulation or peripheral sensorimotor activities) seems to enhance the effects of each intervention by itself.…”
mentioning
confidence: 99%
“…28,29,35,36,38,41 However, other reports did not show measurable therapeutic effects of rTMS on motor function after stroke. [42][43][44] Because of the inconsistent findings and methodological discrepancies across these trials, there is a lack of consensus regarding the effect of rTMS on motor recovery in patients with stroke.…”
mentioning
confidence: 99%
“…Some studies, including randomized double-blind studyand sham stimulationcontrolled trial, have assessed their effects on motor function in people with stroke and TBI. The findings have been inconsistent [51][52][53][54].…”
Section: Transcranial Magnetic Stimulation and Transcranial Direct-cumentioning
confidence: 99%